The conscience industry exploring religious consciousness in the Catholic Mass Media Awards - Cortel, Marijoe Capistrano 1990- (2012)
"My thesis studies how the Catholic Mass Media Awards (CMMA), an arm of the Catholic Church, uses media, particularly broadcast television, in fulfilling the Catholic Church's evangelical mission through the awards it gives out. Specifically, it inquires how the CMMA informs religious consciousness through the finalists and winners in the television category. My study relates the different Catholic teachings embedded and communicated in the programs with Catholic doctrines and Biblical scriptures. It also answers the query if the CMMA favors finalists that validate Catholic ideologies over those that tend to veer away from the teachings of the Roman Catholic Church. The 33rd Catholic Mass Media Awards, with the theme of "Proclaiming the Truth of Life" promulgates four major truths about Catholic consciousness, namely 1) the importance of loving one's family, 2) the need to help other people through charity, 3) the value of forgiveness over vengeance and 4) the Church's emphasis on the importance of faith. Guided by the theory of Louis Althusser's ideological state apparatuses, this study presents the Catholic teachings evident in the stories in the television dramas, life stories of different personalities, topics explored in feature programs, and the dialogue uttered by the characters or hosts."